Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Hasil Belajar Matematika Siswa SMA Kelas XI - Novia Indriyati; Lukman Harun; Heni Purwati; Kresni Winanti (Journal on Education, 2023)
The purpose of this study was to improve the learning outcomes of mathematics students in class XI IPA 1 SMA Negeri 5 Semarang Semester 1 of the 2022/2023 academic year by applying a problem-based learning model on geometric transformation material. This research is a classroom action research conducted in two cycles, each cycle consists of one meeting. The subjects of this study were students of class XI IPA 1, with a total of 36 students. Data acquisition techniques with testing techniques. The data analysis method uses descriptive comparison between Cycle I and Cycle II in the form of a percentage of math learning outcomes. Based on the results of the study, learning by using problem-based learning models can improve student learning outcomes on geometric transformation material in mathematics subjects. The results of the implementation of cycle I showed that only 25 students or 69% were declared complete. There was an increase in cycle II, with 29 students (81%) declared complete in learning math. Since the KKM for this research is 75, then this research is considered successful.